Shoulder pain across more movements is not related to more rotator cuff tendon findings in people with chronic shoulder pain diagnosed with subacromial pain syndrome - Rafael Krasic Alaiti; J.P. Caneiro; Juliana T. Gasparin; Thais Cristina Chaves; Eduardo A. Malavolta; Mauro E.C. Gracitelli; Ann Meulders; Marcelo Fernandes da Costa (PAIN Reports, 2021)
Abstract. Introduction:. People with chronic shoulder pain commonly report pain during arm movements in daily-life activities. Pain related to movement is commonly viewed as an accurate representation of tissue damage. Thus, when a person reports pain across a variety of movements, this is often understood as indicative of greater damage. Objectives:. We aimed to investigate if movement-related pain that occurs across a wider variety of movements was associated with the number or severity of rotator cuff tendons reported as abnormal on a magnetic resonance imaging (MRI). To answer this question, this study was designed in 3 phases. Methods:. We recruited 130 individuals with chronic shoulder pain diagnosed with subacromial pain syndrome. First, a list of daily functional activities commonly reported as painful by people with chronic shoulder pain was generated from 3 well-established outcome measures with 30 individuals and a measurement tool was developed with data from further 100 individuals, which demonstrated to have acceptable content validity, construct validity, internal consistency, interrater reliability, and structural validity. Multiple linear regression was then used to evaluate the hypotheses of the study. A direct acyclic graph was used to select variables for linear regression modelling. Results:. There was no association between movement-related pain occurrence across movements and the MRI findings. Conclusion:. Our study provides evidence that neither the number of rotator cuff tendons reported as abnormal nor the severity of each tendon imaging finding were associated with pain occurrence across movements and activities commonly perceived as painful by people with chronic shoulder pain.